1992
DOI: 10.1152/jappl.1992.72.5.1978
|View full text |Cite
|
Sign up to set email alerts
|

Carotid chemoreceptors, systemic blood pressure, and chronic episodic hypoxia mimicking sleep apnea

Abstract: We have described a rat model that responds to repetitive episodic hypoxia (12-s infusions of nitrogen into daytime sleeping chambers every 30 s, 7 h/day for 35 days) with an increase in diurnal systemic blood pressure. We hypothesized that afferent information from the peripheral chemoreceptors may be necessary to produce diurnal blood pressure elevation in this hypoxia model. Carotid body denervation (CBD) was accomplished by severing both carotid sinus nerves in two groups of male Wistar rats (250-375 g). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
337
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(367 citation statements)
references
References 0 publications
19
337
0
6
Order By: Relevance
“…A much larger difference between groups was found for mean blood pressure, which was higher in n-IH rats compared with controls. This is strikingly similar to the effects of chronic exposure to IH in adults, which also induces hypertension (12). In adults, this depends on the recurrent activation of peripheral chemoreceptors and is prevented by bilateral carotid body denervation during exposure (12,30), and following chemical sympathetic denervation (13).…”
Section: Respiratory and Hemodynamic Variables In Normoxia In Controlsupporting
confidence: 58%
See 1 more Smart Citation
“…A much larger difference between groups was found for mean blood pressure, which was higher in n-IH rats compared with controls. This is strikingly similar to the effects of chronic exposure to IH in adults, which also induces hypertension (12). In adults, this depends on the recurrent activation of peripheral chemoreceptors and is prevented by bilateral carotid body denervation during exposure (12,30), and following chemical sympathetic denervation (13).…”
Section: Respiratory and Hemodynamic Variables In Normoxia In Controlsupporting
confidence: 58%
“…This is strikingly similar to the effects of chronic exposure to IH in adults, which also induces hypertension (12). In adults, this depends on the recurrent activation of peripheral chemoreceptors and is prevented by bilateral carotid body denervation during exposure (12,30), and following chemical sympathetic denervation (13). This is accompanied by an enhanced activity of peripheral chemoreceptors (23,48), chronic sympathetic activation (11,29,31,44), blunted baroreflex responses (3,31), and functional changes in the vascular bed (7).…”
Section: Respiratory and Hemodynamic Variables In Normoxia In Controlmentioning
confidence: 59%
“…Although a matter of debate, the role of OSAS in the pathogenesis of hypertension is strongly suggested [11,27] , involving markers or pathways indicative of systemic inflammation, such as CRP. Furthermore, in animal studies intermittent hypoxia has been shown to produce hypertension [28,29] . Cardiac arrhythmias appear to be a common in OSAS patients; still their true prevalence remains unknown.…”
Section: Is Crp Part Of the Link Between Cvd And Osas?mentioning
confidence: 99%
“…Chronic intermittent hypoxia (CIH) and activation of arterial carotid body chemoreceptors are primarily responsible for driving the increase in sympathetic activity [4,17]. The excessive sympathetic activity and hypertension are sustained and contribute to high morbidity and mortality in afflicted patients [15,19].…”
mentioning
confidence: 99%
“…Nonetheless, CIH increases sympathetic nerve activity and blood pressure in healthy young animals [4,17]. Therefore, absence of disease and risk factors is unlikely to account for the normal function in elite divers.…”
mentioning
confidence: 99%